2011
DOI: 10.1364/ao.50.001197
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of droplet sizing based on the ratio of fluorescent and scattered light intensities (LIF/Mie technique)

Abstract: The dependence of fluorescent and scattered light intensities from spherical droplets on droplet diameter was evaluated using Mie theory. The emphasis is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…The advantage of this method in reduced measuring times comes along with various challenging issues, such as accuracy limited by multiple-scattering, absorption effects and calibration procedures [10]. The calibration procedure is especially difficult for 90 deg detection angle since increase of the scattered light intensity with the droplet diameter is irregular [11]. Therefore, LIF/Mie ratio results shown in this study shall treated as qualitative indicator, not as direct SMD result.…”
Section: Introductionmentioning
confidence: 96%
“…The advantage of this method in reduced measuring times comes along with various challenging issues, such as accuracy limited by multiple-scattering, absorption effects and calibration procedures [10]. The calibration procedure is especially difficult for 90 deg detection angle since increase of the scattered light intensity with the droplet diameter is irregular [11]. Therefore, LIF/Mie ratio results shown in this study shall treated as qualitative indicator, not as direct SMD result.…”
Section: Introductionmentioning
confidence: 96%
“…Attenuation of the scattered light intensity as it propagates from the illuminated droplets to the detector 3. Multiple scattering of the scattered light initiated from one droplet on other droplets in the spray These have been considered by many researchers and various approaches have been proposed to address them as the measurement accuracy of the LIF/Mie technique (Yeh, Kosaka et al 1993;Sankar, Maher et al 1999) is sensitive to the scattered light intensity (Charalampous and Hardalupas 2011a;Charalampous and Hardalupas 2011b;Charalampous and Hardalupas 2012).…”
Section: Data Processing Methodologymentioning
confidence: 99%
“…A planar droplet sizing technique (also know as optical patternator) has been proposed for the measurement of the Sauter mean diameter (SMD) of spray droplets, based on combined laser-induced fluorescence and scattered light (LIF/Mie) intensity imaging on a plane of a spray determined by a laser sheet (Yeh, Kosaka et al 1993;Kamimoto 1994;Le Gal, Farrugia et al 1999;Sankar, Maher et al 1999;Domann and Hardalupas 2003;Zimmer, Domann et al 2003;Charalampous and Hardalupas 2011a;Charalampous and Hardalupas 2011b). The LIF/Mie technique has a significant advantage over other droplet sizing methods in that it is a planar technique that can size full planes of sprays, while the other methods are limited to "point" (Phase Doppler Velocimetry, PDV), line of sight (laser diffraction), or planes of small cross-sectional areas (Interferometric Laser Imaging Droplet Sizing, ILIDS) of sprays.…”
Section: Introductionmentioning
confidence: 99%
“…This work showed that the scattering angle (Figure 1.c), the droplet size and the refractive index modify the proportionality between the scattering intensity and the droplet surface. In parallel, the influence of the concentration of fluorescent dye on the proportionality between the fluorescence intensity and the droplet volume [4] was demonstrated. Optimum values of the scattering angle and the fluorescent dye concentration were obtained to improve the sizing measurement accuracy [5,6] and recent studies compared the PDS measurements with the PDA ones [3,7].…”
Section: Planar Droplet Sizing (Pds)mentioning
confidence: 99%
“…A concentration of Rhodamine 6G of 1 mg/L was sufficient to give an exploitable fluorescent signal on the intensified camera. [4].…”
Section: Pds Implementation On An Aeronautical Swirled Spraymentioning
confidence: 99%